What Are the Perceived Needs, Lacks, and Wants of Sports Students in Learning English? - Mike Nurmalia Sari; Muhammad Zaim; Havid Ardi (English Department FBS UNP, 2025)
This study aims to investigate the perceived needs, lacks, and wants of sports students in learning English to develop an effective English coursebook tailored to their academic and professional contexts. Despite the significance of English proficiency in sports education, existing materials lack alignment with the unique requirements of sports students, creating a research gap in English for Specific Purposes (ESP) for this field. The study employed a quantitative approach, collecting data through a need’s analysis questionnaire distributed to 100 sports students from three universities—two private universities and one public university—in West Sumatra, Indonesia. The questionnaire, consisting of 132 items divided into necessities, lacks, and wants, was analyzed using a Likert scale. Data collection was conducted online via Google Forms. The findings indicate that students prioritize learning materials with practical applications and project-based approaches, particularly for communication skills and sports-related vocabulary. However, significant gaps were identified in students’ language skills and foundational language components, emphasizing the need for targeted instructional interventions. The study concludes by recommending the development of a specialized ESP coursebook that integrates project-based language learning (PBLL) with sports-specific content to address the identified gaps.